Uma análise sobre a métrica de índice de estado trófico em reservatórios do Ceará, Nordeste do Brasil - Freitas, Luciane Mara Cardoso (2024)
The high number of reservoirs in the State of Ceará, it resulting from the increasing demand for water in regions with a semiarid climate, in a context of conflicts over water use and climate crises, it determines an intense focus on monitoring these waters and accurate assessments of eutrophication processes. With the aim of assisting the management of water resources, the present study proposed to critically analyze the application of usual trophic state metrics for the waters of reservoirs in Ceará. To do this, the study area, the State's river basins and the 93 reservoirs were characterized. Reservoirs data from the years 2015 to 2021 offered by the COGERH agency were used. The variables chosen were: Transparency (Z), Total Nitrogen (N), Total Phosphorus (P), Chlorophyll a (Cla), Total cyanobacteria count (CB) and available volume (VD). Traditional methods of Trophic State Index (TSI) were applied to the data, in addition to Trophic Level Index (TLI) methods. Shannon Entropy was applied as a method of weighting the study variables, and a specific TSI (TSICE) was proposed, as well as the Degree of Trophic Degradation (DTD) for the region. The highest entropy weight found was equivalent to the cyanobacteria count, resulting in values of 0.395; 0.197; 0.126; 0.122; 0.093 and 0.067 for CB, Cla, VD, P, N and Z, respectively. This result demonstrated the importance of CB in the evaluation of reservoirs. TSICE compared to traditional models obtained similar data. The water classes ranged from eutrophic to hypereutrophic states. In this way, the TSICE was able to be replicated and therefore it can be used as a complementary tool in the assessment of eutrophication in the State's reservoirs. The GCT has also proven to be a valuable auxiliary tool, demonstrating even greater sensitivity in classification by including a physical variable, VD, in addition to CB, which is a significant sanitary parameter in the contamination of the State's reserved waters, and also incorporating the variable weights provided by Shannon Entropy.